Carrier copper foil anti-oxidation solution, carrier copper foil, preparation method of carrier copper foil and electronic product
By using the carrier copper foil anti-oxidation solution to the surface of the copper foil layer, the problem of oxidation of the carrier copper foil in a high temperature environment is solved, its oxidation resistance and binding force with the substrate are improved, and the service life of the electronic components is extended.
Patent Information
- Application Number
- CN202411799051.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-14
AI Technical Summary
The carrier copper foil is prone to oxidation reactions under high temperature environments, resulting in a decrease in electrical conductivity and thermal conductivity, and a decrease in bonding force with the substrate, affecting the performance of electronic components.
A protective film is formed to improve the anti-oxidation performance of a carrier copper foil, including phytic acid, zinc, nickel and nitric acid.
It effectively improves the anti-oxidation performance of the carrier copper foil at high temperatures, maintains the electrical and thermal conductivity of the copper foil, enhances the bonding force with the substrate, and extends the service life of the electronic components.
Smart Images

Figure CN119615173A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the technical field of carrier copper foil, and in particular to a carrier copper foil anti-oxidation solution, a carrier copper foil, and a preparation method and application thereof. Background Art
[0002] With the rapid development of electronic technology, electronic products are developing towards miniaturization, lightness and high performance, and the requirements for electronic materials are getting higher and higher. As one of the important basic materials in the electronics industry, the performance of copper foil directly affects the quality and performance of electronic products. In high-end electronic products, the application of carrier copper foil with ultra-thin copper foil layer is becoming more and more extensive.
[0003] In the preparation and application process of carrier copper foil, the quality of its anti-oxidation performance directly affects the quality and service life of the product. Traditional carrier copper foil is prone to oxidation reaction in high temperature environment, such as in the process of hot pressing and laminating with the substrate, which leads to the decrease of electrical conductivity and thermal conductivity of the copper foil, and significantly reduces the bonding force between the foil and the substrate, thus affecting the performance of the entire electronic component.
[0004] It should be noted that the information disclosed in the above background technology section is only used to enhance the understanding of the background of the present disclosure, and therefore may include information that does not constitute the prior art known to ordinary technicians in the field. Summary of the invention
[0005] According to a first aspect of the present disclosure, a carrier copper foil anti-oxidation solution is provided, which comprises the following components: 1 g / L to 5 g / L phytic acid, 1 g / L to 10 g / L zinc, 1 g / L to 5 g / L nickel, 0.1 g / L to 5 g / L nitric acid, and a solvent.
[0006] In an exemplary embodiment of the present disclosure, based on the above-mentioned solution, the concentration of chromium in the carrier copper foil anti-oxidation solution is 0.
[0007] In an exemplary embodiment of the present disclosure, based on the above solution, the pH value of the carrier copper foil anti-oxidation solution is 1-5.
[0008] In an exemplary embodiment of the present disclosure, based on the above scheme, the solvent is water.
[0009] According to a second aspect of the present disclosure, a method for preparing a carrier copper foil is provided, comprising the following steps:
[0010] Prepare a peeling layer on the surface of the carrier layer to obtain a first pre-finished product;
[0011] Preparing a copper foil layer on a side of the release layer of the first pre-finished product away from the carrier layer to obtain a second pre-finished product;
[0012] The surface of the copper foil layer of the second pre-product is subjected to an anti-oxidation treatment using the anti-oxidation solution of the first aspect.
[0013] In an exemplary embodiment of the present disclosure, based on the above scheme, the current density of the anti-oxidation treatment is 0.1A / dm 2 ~10A / dm 2 .
[0014] In an exemplary embodiment of the present disclosure, based on the above scheme, the temperature of the anti-oxidation treatment is 20°C to 25°C.
[0015] In an exemplary embodiment of the present disclosure, based on the above solution, the transmission speed of the second pre-product in the anti-oxidation treatment is 0.2 m / min to 15 m / min.
[0016] According to a third aspect of the present disclosure, a carrier copper foil is provided, which is prepared by the preparation method of the second aspect.
[0017] According to a fourth aspect of the present disclosure, an electronic product is provided, comprising the copper foil layer of the carrier copper foil of the third aspect.
[0018] It can be seen from the above technical solution that the present disclosure has the following advantages and positive effects:
[0019] 1. In the present disclosure, an anti-oxidation solution for a carrier copper foil is designed. By combining phytic acid, zinc, nickel and nitric acid, a solution having a good anti-oxidation effect on the carrier copper foil can be obtained. In particular, after the carrier copper foil is subjected to an anti-oxidation treatment using the solution, the anti-oxidation performance of the carrier copper foil at high temperatures can be effectively improved, so that the carrier copper foil maintains stable performance when hot-pressed with the substrate, and the bonding force between the carrier copper foil and the substrate is effectively improved.
[0020] 2. After the carrier copper foil is subjected to anti-oxidation treatment by the anti-oxidation solution disclosed in the present invention, the carrier copper foil can maintain good electrical and thermal conductivity. After the carrier copper foil is applied to electronic components, the electronic components can maintain good performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] The above and other features and advantages of the present disclosure will become more apparent by describing in detail example embodiments thereof with reference to the attached drawings.
[0022] Figure 1 It is a schematic structural diagram of a carrier copper foil roughening device in an embodiment of the present disclosure.
[0023] Figure 2 It is a schematic structural diagram of a carrier copper foil in an embodiment of the present disclosure.
[0024] The main components in the figure are described as follows:
[0025] 1. Carrier copper foil roughening equipment; 2. First roughening tank; 3. Second roughening tank; 4. Transfer roller; 5. First carrier copper foil; 6. Second carrier copper foil; 61. Carrier layer; 62. Stripping layer; 621. First brush plating layer; 622. Second brush plating layer; 63. Copper foil layer. DETAILED DESCRIPTION
[0026] Example embodiments will now be described more fully with reference to the accompanying drawings. However, example embodiments can be implemented in a variety of forms and should not be construed as limited to the embodiments set forth herein; rather, these embodiments are provided so that this disclosure will be comprehensive and complete and will fully convey the concepts of the example embodiments to those skilled in the art. The same reference numerals in the figures represent the same or similar structures, and thus their detailed description will be omitted.
[0027] In the related carrier copper foil technology, the carrier copper foil is prone to oxidation reaction in a high temperature environment, such as in the process of hot pressing and compounding with the substrate, resulting in a decrease in the electrical conductivity and thermal conductivity of the copper foil, and significantly reducing the bonding force with the substrate, thereby affecting the performance of the entire electronic component. In order to solve this problem, the embodiment of the present disclosure provides a carrier copper foil anti-oxidation solution. The carrier copper foil anti-oxidation solution includes the following components: phytic acid 1g / L~5g / L, zinc 1g / L~10g / L, nickel 1g / L~5g / L, nitric acid 0.1g / L~5g / L and solvent. In this embodiment, by combining phytic acid, zinc, nickel and nitric acid, a solution with good anti-oxidation effect on the carrier copper foil can be obtained. In particular, after the carrier copper foil is subjected to anti-oxidation treatment using the solution, the anti-oxidation performance of the carrier copper foil at high temperature can be effectively improved, so that the carrier copper foil maintains stable performance when hot pressing and compounding with the substrate, and effectively promotes the improvement of the bonding force between the carrier copper foil and the substrate. At the same time, after the carrier copper foil is subjected to anti-oxidation treatment by the solution, the carrier copper foil can maintain good electrical and thermal conductivity. After the carrier copper foil is applied to electronic components, the electronic components can maintain good performance.
[0028] Furthermore, the protective film formed by the anti-oxidation solution disclosed in the present invention can improve the corrosion resistance of the copper foil. The complex formed by phytic acid and metal ions can fill the tiny pores on the surface of the copper foil, making the surface of the copper foil smoother and flatter, reducing the adhesion and penetration of the corrosive medium on the surface of the copper foil, thereby enhancing the resistance of the copper foil to corrosive media such as acids, alkalis, and salts.
[0029] The anti-oxidation solution disclosed in the present invention can make the copper foil surface more uniform and smooth, and reduce the surface roughness. The deposition of metal ions such as zinc and nickel on the copper foil surface can fill the surface unevenness, making the copper foil surface smoother, which is beneficial to subsequent processing and application, such as coating, printing and other processes, and improving the quality and consistency of the product.
[0030] The components in the anti-oxidation solution disclosed in the present invention react chemically with the surface of the copper foil to form chemical bonds or strong physical adsorption, thereby improving the bonding force between the protective film and the copper foil substrate, making the protective film less likely to fall off during use, and being able to better play its protective role and maintain the stability of the copper foil performance.
[0031] Furthermore, the formation of the protective film can reduce the oxidation and impurity adsorption on the surface of the copper foil, thereby facilitating the transmission of electrons and making the conductivity of the copper foil more stable.
[0032] Specifically, phytic acid is an organic acid with strong chelating ability, and its molecular structure contains multiple phosphate groups. In the anti-oxidation solution, phytic acid can quickly react with copper ions on the surface of copper foil to form a tightly packed protective film with certain barrier properties. At the same time, the hydroxyl and phosphate groups of phytic acid can also complex with zinc ions and nickel ions, further strengthening the structural integrity and stability of the protective film, making it less likely to be destroyed in high temperature environments.
[0033] Zinc ions have a dual role in the solution. On the one hand, zinc is relatively chemically active and can undergo a certain degree of replacement reaction on the surface of the copper foil to form a zinc protective film. This zinc layer can act as a sacrificial anode and preferentially undergo oxidation reaction with oxygen in the surrounding environment, thereby delaying the oxidation process of the copper foil. On the other hand, after zinc ions are complexed with phytic acid, they can be evenly dispersed in the protective film, enhancing the overall protective performance of the protective film.
[0034] Nickel ions can form alloy phases or intermetallic compounds with phytic acid and copper atoms on the surface of copper foil. This special structure can significantly improve the hardness, wear resistance and high-temperature oxidation resistance of the protective film. Under high temperature conditions, the presence of nickel helps maintain the structural stability of the protective film and prevents it from softening, cracking or decomposing, thereby providing long-lasting and reliable protection for the copper foil.
[0035] Nitric acid plays a major role in adjusting the pH of the solution and promoting the dissolution and reaction of metal ions. By controlling the content of nitric acid, the reaction activity of the solution can be optimized to ensure that phytic acid, zinc ions and nickel ions can be fully dissolved and evenly distributed in the solvent, so that they can react efficiently when in contact with copper foil, forming a uniform, dense and high-performance anti-oxidation protective film.
[0036] Furthermore, after the carrier copper foil is treated with the anti-oxidation solution disclosed in the present invention, the application of the carrier copper foil can be effectively improved.
[0037] For example, in the field of electronic circuits, the improvement of surface quality and the stabilization of conductivity enable copper foil to better meet the requirements of high-precision and high-performance electronic devices when used as a conductive material in electronic circuits. For example, in the manufacture of printed circuit boards (PCBs), copper foil treated with the anti-oxidation solution disclosed in the present invention can improve the accuracy and reliability of circuits, reduce the loss and interference of signal transmission, and help improve the performance and quality of electronic products.
[0038] For another example, in the field of lithium batteries, copper foil treated with the anti-oxidation solution disclosed in the present invention has good antioxidant and corrosion resistance, so that when the copper foil is used as the negative electrode current collector of the lithium battery, it can better adapt to the complex chemical environment inside the lithium battery, and reduce the battery performance degradation caused by oxidation and corrosion of the copper foil, such as increased internal resistance, capacity attenuation and other problems, thereby improving the cycle life and safety of the lithium battery, which is conducive to the widespread application of lithium batteries in new energy vehicles, energy storage and other fields.
[0039] For another example, copper foil treated with the anti-oxidation solution disclosed in the present invention can also be widely used in photovoltaic, communication and other fields. Its excellent performance can meet the requirements of these fields for material reliability and stability, provide guarantee for the stable operation of related equipment and systems, and promote technological development and application expansion in these fields.
[0040] It can be understood that in the antioxidant solution of the present disclosure, the concentration of each component is expressed based on the volume of the solution, and the mass of each component is based on the concentration corresponding to the volume of the solution.
[0041] The concentration of phytic acid in the anti-oxidation solution refers to the concentration of the mass of phytic acid based on the volume of the anti-oxidation solution. Optionally, the concentration of phytic acid can be 1g / L, 1.5g / L, 2g / L, 2.5g / L, 3g / L, 3.5g / L, 4g / L, 4.5g / L, 5g / L, etc. It is understood that the concentration of phytic acid can also be other suitable selections within the range of 1g / L to 5g / L.
[0042] The concentration of zinc in the anti-oxidation solution means the concentration of the mass of zinc based on the volume of the anti-oxidation solution. Optionally, the concentration of zinc can be 1g / L, 1.5g / L, 2g / L, 2.5g / L, 3g / L, 3.5g / L, 4g / L, 4.5g / L, 5g / L, 5.5g / L, 6g / L, 6.5g / L, 7g / L, 7.5g / L, 8g / L, 8.5g / L, 9g / L, 9.5g / L, 10g / L, etc. It is understood that the concentration of zinc can also be other suitable selections within the range of 1g / L to 10g / L.
[0043] The concentration of nickel in the anti-oxidation solution refers to the concentration of the mass of nickel based on the volume of the anti-oxidation solution. Optionally, the concentration of nickel can be 1g / L, 1.5g / L, 2g / L, 2.5g / L, 3g / L, 3.5g / L, 4g / L, 4.5g / L, 5g / L, etc. It is understood that the concentration of nickel can also be other suitable selections within the range of 1g / L to 5g / L.
[0044] The concentration of nitric acid in the anti-oxidation solution means the concentration of the mass of nitric acid based on the volume of the anti-oxidation solution. Optionally, the concentration of nitric acid can be 0.1 g / L, 0.2 g / L, 0.3 g / L, 0.4 g / L, 0.5 g / L, 0.6 g / L, 0.7 g / L, 0.8 g / L, 0.9 g / L, 1 g / L, 1.5 g / L, 2 g / L, 2.5 g / L, 3 g / L, 3.5 g / L, 4 g / L, 4.5 g / L, 5 g / L, etc. It is understood that the concentration of nitric acid can also be other suitable selections within the range of 0.1 g / L to 5 g / L.
[0045] In an exemplary embodiment of the present disclosure, the concentration of chromium in the carrier copper foil anti-oxidation solution is 0. In this embodiment, by designing the carrier copper foil anti-oxidation solution, the anti-oxidation solution can maintain a good anti-oxidation effect without using toxic metal chromium. Therefore, the carrier copper foil anti-oxidation solution of the present disclosure is environmentally friendly and is conducive to promoting the green development of carrier copper foil production.
[0046] In an exemplary embodiment of the present disclosure, the pH value of the carrier copper foil anti-oxidation solution is 1 to 5. Within this pH value range, phytic acid, zinc, nickel and nitric acid can cooperate better to further improve the anti-oxidation effect of the solution on the carrier copper foil. It is understandable that the pH value of the carrier copper foil anti-oxidation solution can be adjusted by nitric acid. Optionally, the pH value of the carrier copper foil anti-oxidation solution can be 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, etc. It is understandable that the pH value of the carrier copper foil anti-oxidation solution can also be other suitable choices within the range of 1 to 5.
[0047] In an exemplary embodiment of the present disclosure, the solvent of the carrier copper foil anti-oxidation solution is water. Using water as the solvent can obtain a carrier copper foil anti-oxidation solution with uniform and stable concentration.
[0048] The present disclosure also provides a method for preparing a carrier copper foil, comprising the following steps: preparing a peeling layer on the surface of a carrier layer to obtain a first pre-finished product; preparing a copper foil layer on a side of the peeling layer of the first pre-finished product away from the carrier layer to obtain a second pre-finished product; and performing an anti-oxidation treatment on the surface of the copper foil layer of the second pre-finished product using an anti-oxidation solution.
[0049] In an exemplary embodiment of the present disclosure, based on the above scheme, the current density of the anti-oxidation treatment is 0.1A / dm 2 ~10A / dm 2 If the current density is too small or too large, it is difficult to form a dense anti-oxidation film, which is not conducive to improving the anti-oxidation effect. Optionally, the current density of the anti-oxidation treatment can be 0.1A / dm 2 , 0.2A / dm 2 , 0.5A / dm 2 , 0.8A / dm 2 , 1A / dm 2 , 2A / dm 2 、3A / dm 2 , 4A / dm 2 , 5A / dm 2 、6A / dm 2 , 7A / dm 2 , 8A / dm 2 、9A / dm 2 、10A / dm 2 It is understood that the current density of the anti-oxidation treatment can also be 0.1A / dm 2 ~10A / dm 2 Make other appropriate choices within the scope.
[0050] In an exemplary embodiment of the present disclosure, the temperature of the anti-oxidation treatment is 20°C to 25°C. If the temperature of the anti-oxidation treatment is too low or too high, it is difficult to form a dense anti-oxidation film, which is not conducive to improving the anti-oxidation effect. In this embodiment, anti-oxidation treatment at room temperature can provide a good anti-oxidation effect for the carrier copper foil. Optionally, the temperature of the anti-oxidation treatment can be 20°C, 21°C, 22°C, 23°C, 24°C, 25°C, etc. It is understandable that the temperature of the anti-oxidation treatment can also be other suitable selections within the range of 20°C to 25°C.
[0051] In an exemplary embodiment of the present disclosure, based on the aforementioned scheme, the transmission speed of the first pre-finished product in the anti-oxidation treatment is 0.2m / min to 15m / min. If the transmission speed of the first pre-finished product is too low, the production efficiency is low, and if the transmission speed of the first pre-finished product is too high, it is difficult to form a good anti-oxidation film. Optionally, the transmission speed of the first pre-finished product in the anti-oxidation treatment can be 0.2m / min, 0.5m / min, 0.8m / min, 1m / min, 2m / min, 5m / min, 8m / min, 10m / min, 12m / min, 15m / min, etc. It is understandable that the transmission speed of the first pre-finished product in the anti-oxidation treatment can also be other suitable selections within the range of 0.2m / min to 15m / min.
[0052] In an exemplary embodiment of the present disclosure, preparing the peeling layer includes the following steps: using liquid medicine A to perform a first brush plating on the surface of the carrier layer to form a phosphide film on the surface of the carrier layer; using liquid medicine B to perform a second brush plating on the surface of the phosphide film away from the carrier layer to form a phosphide layer on the surface of the phosphide film. Liquid medicine A includes phosphate, and the phosphate includes at least one of zinc dihydrogen phosphate, calcium dihydrogen phosphate, manganese dihydrogen phosphate, iron dihydrogen phosphate, ammonium dihydrogen phosphate, lithium dihydrogen phosphate, sodium dihydrogen phosphate and potassium dihydrogen phosphate. Liquid medicine B includes a phosphide metal, and the phosphide metal includes at least one of molybdenum phosphide, zinc phosphide, nickel phosphide, chromium phosphide and potassium phosphide.
[0053] In the present disclosure, a stable peeling layer can be formed on the carrier layer by using potions A and B, which is convenient for the subsequent deposition of ultra-thin copper foil. At the same time, after the ultra-thin copper foil is prepared, the peeling layer can show good peeling performance and is easy to peel off from the carrier layer. Specifically, the phosphate in potion A has good chemical stability and adhesion, and can react chemically with the surface of the carrier layer to form a dense phosphating film. The metal phosphide in potion B has good conductivity and peeling performance, and can interact with the phosphating film to form a stable peeling layer structure, so that the ultra-thin copper foil can be easily peeled off from the carrier layer after preparation.
[0054] Different phosphates have different properties. For example, zinc dihydrogen phosphate has good corrosion resistance and adhesion. Calcium dihydrogen phosphate can improve the hardness and wear resistance of the coating. Manganese dihydrogen phosphate can enhance the oxidation resistance of the coating, etc. By selecting different phosphate combinations, the properties of the stripping layer can be adjusted according to specific application requirements.
[0055] Different phosphide metals also have different properties. For example, molybdenum phosphide has good conductivity and high temperature resistance. Zinc phosphide has good corrosion resistance and stripping performance. Nickel phosphide can improve the hardness and wear resistance of the stripping layer. By selecting different phosphide metals for combination, the performance of the stripping layer can be further optimized.
[0056] In an exemplary embodiment of the present disclosure, the molar ratio of phosphorus in potion A to phosphorus in potion B is 3 to 5: 1. Alternatively, the molar ratio of phosphorus in potion A to phosphorus in potion B may be 3: 1, 3.5: 1, 4: 1, 4.5: 1, 5: 1. It is understood that the molar ratio of phosphorus in potion A to phosphorus in potion B may also be other suitable selections within the range of 3 to 5: 1.
[0057] In an exemplary embodiment of the present disclosure, the concentration of phosphate in the potion A is 0.1 g / L to 10 g / L. Optionally, the concentration of phosphate in the potion A can be 0.1 g / L, 0.5 g / L, 1 g / L, 2 g / L, 5 g / L, 8 g / L, 10 g / L. It is understood that the concentration of phosphate in the potion A can also be other suitable selections within the range of 0.1 g / L to 10 g / L.
[0058] In an exemplary embodiment of the present disclosure, the concentration of the metal phosphide in the potion B is 0.2 g / L to 20 g / L. Optionally, the concentration of the metal phosphide in the potion B can be 0.2 g / L, 0.5 g / L, 1 g / L, 2 g / L, 5 g / L, 8 g / L, 10 g / L, 12 g / L, 15 g / L, 18 g / L, 20 g / L. It is understandable that the concentration of the metal phosphide in the potion B can also be other suitable selections within the range of 0.2 g / L to 20 g / L.
[0059] In an exemplary embodiment of the present disclosure, the pH of the liquid medicine A is 1 to 4. Optionally, the pH of the liquid medicine A can be 1, 2, 3, or 4. It is understood that other suitable choices can be made within the pH range of 1 to 4 for the liquid medicine A. Optionally, the pH of the liquid medicine A can be adjusted with phosphoric acid.
[0060] In an exemplary embodiment of the present disclosure, the pH of the medicine B is 1 to 6. Optionally, the pH of the medicine B can be 1, 2, 3, 4, 5, 6. It is understood that other suitable choices can be made within the pH range of 1 to 6 for the medicine B. Optionally, the pH of the medicine B can be adjusted with phosphoric acid.
[0061] It is understood that the concentration of phosphate in solution A means the concentration of phosphate by mass based on the volume of solution A. The concentration of metal phosphide in solution B means the concentration of metal phosphide by mass based on the volume of solution B.
[0062] Optionally, the solvent in both medicine solution A and medicine solution B is water.
[0063] In the present disclosure, the formed phosphating film helps to reduce the adhesion between the copper foil layer and the carrier layer in the subsequent stripping process, thereby achieving smooth stripping of the copper foil layer, and improving the corrosion resistance and surface properties of the stripping layer, and enhancing its bonding with subsequent coatings or plating layers. The phosphide layer further enhances the corrosion resistance and electrical conductivity of the stripping layer, while improving the mechanical strength and adhesion of the stripping layer.
[0064] In the present disclosure, liquid medicine A and liquid medicine B respectively form a phosphide film and a phosphide layer on the surface of the carrier layer in sequence. The preparation method is simple and easy, does not need to rely on complex processes and expensive equipment, and is easy to promote.
[0065] Optionally, the material of the carrier layer in the present disclosure may be copper, aluminum, zinc, nickel or other materials that can be generated by electrolysis.
[0066] In some embodiments, the thickness of the phosphide film is 0.5nm to 20nm, and the thickness of the phosphide layer is 5nm to 50nm. If the thickness of the phosphide film is too small, it is difficult to provide a good foundation for the formation of the phosphide layer. If the thickness of the phosphide film is too large, the overall thickness of the stripping layer will be too large, which will increase the difficulty of stripping the stripping layer in the later stage. At the same time, if the thickness of the phosphide film is too large, it will also cause a large waste of resources and increase the manufacturing cost of the carrier copper foil stripping layer. Optionally, the thickness of the phosphide film can be 0.5nm, 1nm, 5nm, 8nm, 10nm, 12nm, 15nm, 18nm, 20nm. If the thickness of the phosphide layer is too small, the bonding force between the copper foil and the stripping layer may be reduced, affecting the preparation of the copper foil. If the thickness of the phosphide layer is too large, the overall thickness of the stripping layer will be too large, which will increase the difficulty of stripping the stripping layer in the later stage. At the same time, if the thickness of the phosphide layer is too large, it will also cause a large waste of resources and increase the manufacturing cost of the carrier copper foil stripping layer. Optionally, the thickness of the phosphide layer may be 5 nm, 10 nm, 15 nm, 20 nm, 30 nm, 40 nm, or 50 nm.
[0067] In an exemplary embodiment of the present disclosure, the temperature of medicine A is 20°C to 50°C. Alternatively, the temperature of medicine A may be 20°C, 30°C, 40°C, or 50°C. The temperature of medicine B is 30°C to 50°C. Alternatively, the temperature of medicine B may be 30°C, 40°C, or 50°C.
[0068] In an exemplary embodiment of the present disclosure, the first brush plating is non-electrified brush plating. During the first brush plating process, the phosphate in the solution A reacts chemically with the surface of the carrier layer to form a phosphating film. This non-electrified brush plating method can avoid direct contact between the electrode and the carrier layer, reduce damage to the carrier layer, and also improve the uniformity and density of the phosphating film. Optionally, the first brush plating uses a titanium roller to brush the solution A onto the surface of the carrier layer to form a phosphating film.
[0069] In an exemplary embodiment of the present disclosure, the second brush plating is charged pulse brush plating. During the second brush plating process, the phosphide metal in the solution B is deposited on the surface of the phosphide film under the action of the electric field to form a phosphide layer. This charged pulse brush plating method can improve the deposition speed and deposition quality, and can also control the thickness and structure of the phosphide layer.
[0070] Optionally, the pulse of pulse brush plating is any one or combination of positive pulse or negative pulse. Among them, pulse brush plating can refer to an electroplating technology that changes the electroplating process within a wide range by superimposing a specific waveform pulse (such as a rectangular pulse) on a fixed direct current. Positive pulse brush plating can mean that during the electroplating process, the positive direction of the current is periodically connected and disconnected. Negative pulse brush plating can mean that during the electroplating process, the negative direction of the current is periodically connected and disconnected. Pulse brush plating can improve the quality of the coating, such as the flatness and adhesion of the coating.
[0071] In an exemplary embodiment of the present disclosure, the current density of the second brush plating is 0.2A / square decimeter to 1A / square decimeter. Optionally, the current density of the second brush plating can be 0.2A / square decimeter, 0.3A / square decimeter, 0.5A / square decimeter, 0.8A / square decimeter, 1A / square decimeter. Optionally, the second brush plating uses a titanium electrode to brush-plate the solution B onto the surface of the phosphating film away from the carrier layer.
[0072] In an exemplary embodiment of the present disclosure, the preparation of the copper foil layer includes the following steps: electroplating the first pre-finished product with a copper electroplating solution to deposit the copper foil layer on the side of the stripping layer away from the carrier layer; the copper electroplating solution includes the following components: phytic acid 20g / L~100g / L, copper carbonate 10g / L~80g / L and solvent; the pH value of the copper electroplating solution is 0.5~3. By combining phytic acid and copper carbonate at appropriate concentrations and under the condition of a pH value of 0.5~3, copper grains with smaller size and uniform distribution can be obtained, and the number of grain boundaries can be increased. In the deformation process of the copper foil, the grain boundary can play a role in coordinating the deformation, making the material more susceptible to plastic deformation, thereby increasing the elongation of the ultra-thin copper. Electroplating treatment is performed using the above-mentioned copper electroplating solution to deposit the copper foil layer on the surface of the stripping layer away from the carrier layer, and a copper foil layer with ultra-thin thickness and high elongation can be obtained, which broadens the scope of use of the carrier copper foil.
[0073] It can be understood that in the copper electrolyte of the present disclosure, the concentration of each component is expressed based on the volume of the copper electrolyte, and the mass of each component is based on the concentration of the volume of the copper electrolyte.
[0074] The concentration of phytic acid indicates the concentration of the mass of phytic acid based on the volume of the copper electrolyte. Optionally, the concentration of phytic acid can be, but is not limited to, 20 g / L, 25 g / L, 30 g / L, 35 g / L, 40 g / L, 45 g / L, 50 g / L, 55 g / L, 60 g / L, 65 g / L, 70 g / L, 75 g / L, 80 g / L, 85 g / L, 90 g / L, 95 g / L, 100 g / L. It is understood that the concentration of phytic acid can also be other suitable selections within the range of 20 g / L to 100 g / L.
[0075] The concentration of copper carbonate indicates the concentration of the mass of copper carbonate based on the volume of the copper electrolyte. Optionally, the concentration of copper carbonate can be, but is not limited to, 10 g / L, 15 g / L, 20 g / L, 25 g / L, 30 g / L, 35 g / L, 40 g / L, 45 g / L, 50 g / L, 55 g / L, 60 g / L, 65 g / L, 70 g / L, 75 g / L, 80 g / L. It is understood that the concentration of copper carbonate can also be other suitable selections within the range of 10 g / L to 80 g / L.
[0076] In some embodiments, the pH value of the copper electrodeposition solution may be, but is not limited to, 0.5, 0.8, 1, 1.2, 1.5, 1.8, 2, 2.2, 2.5, 2.8, or 3. It is understood that the pH value of the copper electrodeposition solution may also be selected in the range of 0.5 to 3. The pH value of the copper electrodeposition solution combined with phytic acid and copper carbonate can produce fine and uniform copper particles by electrodeposition, so that the ultra-thin copper foil layer has a higher elongation.
[0077] In some embodiments, the copper electrodeposition solution further comprises a tartaric acid additive. Optionally, the concentration of the tartaric acid additive is 0.1 g / L to 1 g / L. It is understood that the concentration of the additive represents the concentration of the mass of the additive based on the volume of the copper electrolyte. Optionally, the concentration of the tartaric acid additive can be 0.1 g / L, 0.2 g / L, 0.3 g / L, 0.4 g / L, 0.5 g / L, 0.6 g / L, 0.7 g / L, 0.8 g / L, 0.9 g / L, 1 g / L. It is understood that the concentration of the tartaric acid additive can also be other suitable selections within the range of 0.1 g / L to 1 g / L.
[0078] Furthermore, copper carbonate can be used as a supply source of copper ions to continuously and stably provide copper ions for electrodeposition, ensuring the normal growth of copper foil. The rate of copper ion release is relatively stable, which helps to maintain the smooth progress of the electrodeposition process. Phytic acid and tartaric acid additives can form complexes with copper ions, synergistically control the deposition rate of copper ions, adjust the concentration and existence form of copper ions in the electrodeposition solution, and make the deposition of copper ions on the cathode surface more uniform and delicate, thereby obtaining a copper foil coating with denser crystals and improving its quality and performance.
[0079] In addition, tartaric acid additives can be used as grain refiners to promote the refinement of copper grains, making the microstructure of the copper foil more uniform, thereby increasing the elongation of the ultra-thin copper foil, making it more suitable for applications with high requirements on material performance, such as high-performance electronic devices.
[0080] At the same time, the tartaric acid additive can play the role of buffering the pH of the solution and maintain the relative stability of the pH value of the electrodeposition solution. During the electrodeposition process, as copper ions continue to deposit, the pH value of the solution may change, and the tartaric acid additive can slow down the fluctuation of the pH value through its own acid-base balance, providing a stable chemical environment for the electrodeposition reaction, thereby ensuring the quality and performance stability of the ultra-thin copper foil.
[0081] Furthermore, during the electrodeposition process, some impurity ions may exist, and the tartaric acid additive can react with these impurity ions to reduce the adsorption and deposition of the impurity ions on the cathode surface, thereby reducing the impact of impurities on the quality of the ultra-thin copper foil and improving the purity of the ultra-thin copper foil.
[0082] In some embodiments, the solvent of the copper electrodeposition solution is water.
[0083] In some embodiments, the temperature of the copper electrodeposition liquid during the electrodeposition treatment is 35°C to 60°C. If the temperature of the copper electrodeposition liquid is too low, it is difficult to obtain a good electrodeposition effect. If the temperature of the copper electrodeposition liquid is too high, on the one hand, it will produce higher energy consumption, and on the other hand, it will make the electrodeposition speed too fast, which increases the risk of uneven accumulation of copper particles. Optionally, the temperature of the copper electrodeposition liquid during the electrodeposition treatment is 35°C, 40°C, 45°C, 50°C, 55°C, or 60°C. It is understandable that the temperature of the copper electrodeposition liquid during the electrodeposition treatment can also be selected in the range of 35°C to 60°C.
[0084] In some embodiments, the rate of the electroplating treatment is 0.3 m / min to 1.2 m / min. If the rate of the electroplating treatment is too high, it is difficult to obtain a copper foil layer that meets the thickness requirements. If the rate of the electroplating treatment is too low, the thickness of the copper foil layer may be too large, which is difficult to meet the thickness requirements of the ultra-thin copper foil, and will also cause more waste of resources. Optionally, the rate of the electroplating treatment can be 0.3 m / min, 0.4 m / min, 0.5 m / min, 0.6 m / min, 0.7 m / min, 0.8 m / min, 0.9 m / min, 1 m / min, 1.1 m / min, 1.2 m / min. It is understandable that the rate of the electroplating treatment can also be other suitable selections within the range of 0.3 m / min to 1.2 m / min.
[0085] In some embodiments, the current density of the electrodeposition process is 1 A / dm 2 ~10A / dm 2 If the current density of the electroplating treatment is too small, it is difficult to obtain a high electroplating efficiency. If the current density of the electroplating treatment is too large, it is difficult to obtain a copper foil layer with good consistency. Optionally, the current density of the electroplating treatment can be 1A / dm 2 , 2A / dm 2、3A / dm 2 , 4A / dm 2 , 5A / dm 2 、6A / dm 2 , 7A / dm 2 , 8A / dm 2 、9A / dm 2 、10A / dm 2 It is understood that the current density of the electrodeposition process can also be 1A / dm 2 ~10A / dm 2 Make other appropriate choices within the scope.
[0086] In an exemplary embodiment of the present disclosure, after preparing the copper foil layer and before the anti-oxidation treatment, the method further includes: performing a roughening treatment on the copper foil layer.
[0087] In an exemplary embodiment of the present disclosure, the roughening treatment includes the following steps: performing a first roughening treatment and a second roughening treatment on the second pre-finished product in sequence; the first roughening treatment uses a first roughening solution, and the second roughening treatment uses a second roughening solution; the first roughening solution includes the following components: 20g / L~25g / L copper, 30g / L~50g / L sulfuric acid, 0.1g / L~1g / L additives and a solvent; the additives include at least one of carbon nanotubes and non-magnetic metal inorganic salts; the second roughening solution includes the following components: 20g / L~25g / L copper, 30g / L~50g / L sulfuric acid, 0.1g / L~1g / L additives and a solvent; the additives include at least one of carbon nanotubes and non-magnetic metal inorganic salts.
[0088] In order to improve the bonding force between the copper foil layer of the carrier copper foil and substrates such as epoxy resin, PPO, PTFE, etc., the prior art often adopts a method of increasing the surface roughness of the copper foil layer of the carrier copper foil. When the surface roughness of the carrier copper foil layer is increased, the copper foil layer can be better attached to the surface of the substrate, thereby improving the bonding force between the copper foil layer and the substrate. However, since the copper foil layer of the carrier copper foil is usually an ultra-thin copper foil, blindly increasing the surface roughness may destroy the intrinsic properties of the ultra-thin copper foil. For example, when the surface roughness of the ultra-thin copper foil increases, the flatness of the ultra-thin copper foil decreases, and the concave-convex degree of the copper foil surface becomes larger, which will cause the strength of the ultra-thin copper foil in the concave position to decrease, thereby affecting the normal use of the ultra-thin copper foil. That is, in order to keep the ultra-thin copper foil with good intrinsic properties, it is actually difficult to further improve the bonding force between the ultra-thin copper foil and the substrate by increasing the surface roughness.
[0089] When the carrier copper foil is roughened by the roughening solution disclosed in the present invention, the surface area of the copper foil layer of the carrier copper foil can be increased while the copper foil layer of the carrier copper foil has a suitable surface roughness, thereby improving the bonding force between the copper foil layer of the carrier copper foil and the substrate. That is, unlike the existing method of simply improving the surface roughness of the copper foil layer of the carrier copper foil, the roughening solution disclosed in the present invention can make the copper foil layer of the carrier copper foil have a suitable surface roughness so that the copper foil layer of the carrier copper foil can maintain a good strength. On the basis of making the copper foil layer of the carrier copper foil have a suitable roughness, the surface area of the copper foil layer of the carrier copper foil can be increased by the roughening solution disclosed in the present invention. When the surface area of the copper foil layer of the carrier copper foil is increased, the bonding force between the copper foil layer and the substrate can be effectively improved. For example, compared with the existing roughening solution, the roughening solution in some embodiments of the present invention can increase the surface area of the carrier copper foil layer by 200% to 500% on the basis of obtaining a roughness similar to that of the existing roughening solution, thereby greatly improving the bonding force between the copper foil layer and the substrate. The two-stage roughening method is used to roughen the carrier copper foil, which can form a relatively suitable surface roughness on the surface of the copper foil layer of the carrier copper foil, while making the copper foil layer of the carrier copper foil have a larger surface area, effectively increasing the bonding force between the copper foil layer of the carrier copper foil and the substrate. In this way, the ultra-thin copper foil layer of the carrier copper foil can maintain a good bonding force with the substrate while maintaining good intrinsic properties.
[0090] Furthermore, the carrier copper foil prepared by the roughening method disclosed in the present invention has the characteristics of ultra-thinness, low roughness, high peel strength and good etching properties, and is suitable for high-end application scenarios such as high-frequency and high-speed copper-clad laminates, flexible printed circuit boards and high-density interconnection technology boards, and can effectively expand the application scope of carrier copper foil in the field of electronic materials. For example, in high-frequency and high-speed circuits, the low roughness and high bonding performance of the carrier copper foil prepared by the roughening method disclosed in the present invention helps to reduce signal transmission loss and improve signal integrity; in flexible printed circuit boards, good etching properties and strength ensure the performance stability of the circuit board under conditions such as bending.
[0091] Furthermore, the two-stage roughening process disclosed in the present invention can make the roughening process more stable and efficient. The appropriate temperature range avoids the problem of excessive energy consumption or poor roughening effect. Reasonable current density and time settings ensure the roughening efficiency while helping to obtain a copper foil layer with good consistency. For example, in large-scale production, the roughening method disclosed in the present invention can stably produce carrier copper foil products with consistent performance, reduce the defective rate caused by product performance fluctuations, and improve production efficiency and economic benefits.
[0092] In the carrier copper foil roughening solution disclosed in the present invention, carbon nanotubes have excellent physical and chemical properties, which can affect the microstructure formation of the copper foil surface during the roughening process; the type of non-magnetic metal inorganic salt also has an important influence on the roughening effect. The various components in the roughening solution work together to effectively increase the surface area of the roughened surface of the carrier copper foil, so that the carrier copper foil has good bonding strength with the substrate.
[0093] It can be understood that in the roughening solution of the present disclosure, the concentration of each component is expressed based on the volume of the roughening solution, and the mass of each component is based on the concentration of the volume of the roughening solution.
[0094] The copper concentration indicates the concentration of the copper mass based on the volume of the roughening solution. Optionally, the copper concentration may be, but is not limited to, 20 g / L, 20.5 g / L, 21 g / L, 21.5 g / L, 22 g / L, 22.5 g / L, 23 g / L, 23.5 g / L, 24 g / L, 24.5 g / L, 25 g / L. It is understood that the copper concentration may also be other suitable selections within the range of 20 g / L to 25 g / L.
[0095] The concentration of sulfuric acid indicates the mass of sulfuric acid based on the volume of the roughening solution. Optionally, the concentration of sulfuric acid can be, but is not limited to, 30 g / L, 32 g / L, 35 g / L, 38 g / L, 40 g / L, 42 g / L, 45 g / L, 48 g / L, 50 g / L. It is understood that the concentration of sulfuric acid can also be other suitable selections within the range of 30 g / L to 50 g / L.
[0096] The concentration of the additive refers to the concentration of the mass of the additive based on the volume of the roughening solution. Optionally, the concentration of the additive can be, but is not limited to, 0.1 g / L, 0.2 g / L, 0.3 g / L, 0.4 g / L, 0.5 g / L, 0.6 g / L, 0.7 g / L, 0.8 g / L, 0.9 g / L, 1 g / L. It is understood that the concentration of the additive can also be other suitable selections within the range of 0.1 g / L to 1 g / L.
[0097] Optionally, the first roughening solution and the second roughening solution may be the same or different.
[0098] In some embodiments, the non-magnetic metal inorganic salt includes at least one of zinc sulfate, zinc chloride, aluminum sulfate, aluminum chloride, magnesium sulfate, magnesium chloride, calcium carbonate and calcium chloride. That is, the additive includes at least one of carbon nanotubes, zinc sulfate, zinc chloride, aluminum sulfate, aluminum chloride, magnesium sulfate, magnesium chloride, calcium carbonate and calcium chloride. Optionally, the additive is carbon nanotubes.
[0099] In some embodiments, the solvent of the first roughening solution and the second roughening solution is water.
[0100] In some embodiments, the temperature of the roughening solution in the first roughening treatment is 15°C to 20°C. If the temperature of the roughening solution is too low, it is difficult to obtain a good roughening effect. If the temperature of the roughening solution is too high, on the one hand, it will produce higher energy consumption, and on the other hand, the roughening speed will be too fast, and it will be difficult to control the stable growth of the surface area of the copper foil layer of the carrier copper foil. Optionally, the temperature of the roughening solution in the first roughening treatment is 15°C, 16°C, 17°C, 18°C, 19°C, 20°C. It is understandable that the temperature of the roughening solution in the first roughening treatment can also be selected in the range of 15°C to 20°C.
[0101] In some embodiments, the current density of the first roughening treatment is 70A / square decimeter to 100A / square decimeter. If the current density of the first roughening treatment is too small, it is difficult to obtain a high roughening efficiency, and if the current density of the first roughening treatment is too large, it is difficult to obtain a copper foil layer with good consistency. Optionally, the current density of the first roughening treatment can be 70A / square decimeter, 80A / square decimeter, 90A / square decimeter, 100A / square decimeter, etc.
[0102] In some embodiments, the first roughening treatment lasts for 10 seconds to 50 seconds. If the first roughening treatment lasts for too short a time, it is difficult to obtain a good roughening effect. If the first roughening treatment lasts for too long a time, on the one hand, it will generate high energy consumption, and on the other hand, it may cause excessive damage to the copper foil layer of the carrier copper foil, affecting the performance of the copper foil layer. Optionally, the first roughening treatment time can be 10 seconds, 20 seconds, 30 seconds, 40 seconds, 50 seconds, etc.
[0103] In some embodiments, the temperature of the roughening solution in the second roughening treatment is 15°C to 20°C. If the temperature of the roughening solution is too low, it is difficult to obtain a good roughening effect. If the temperature of the roughening solution is too high, on the one hand, it will produce higher energy consumption, and on the other hand, the roughening speed will be too fast, and it will be difficult to control the stable growth of the surface area of the copper foil layer of the carrier copper foil. Optionally, the temperature of the roughening solution in the second roughening treatment is 15°C, 16°C, 17°C, 18°C, 19°C, 20°C. It is understandable that the temperature of the roughening solution in the second roughening treatment can also be selected in the range of 15°C to 20°C.
[0104] In some embodiments, the current density of the second roughening treatment is 10A / square decimeter to 30A / square decimeter. If the current density of the second roughening treatment is too small, it is difficult to obtain a high roughening efficiency, and if the current density of the second roughening treatment is too large, it is difficult to obtain a copper foil layer with good consistency. Optionally, the current density of the second roughening treatment can be 10A / square decimeter, 15A / square decimeter, 20A / square decimeter, 25A / square decimeter, 30A / square decimeter, etc.
[0105] In some embodiments, the second roughening treatment time is 10S to 50S. If the second roughening treatment time is too short, it is difficult to obtain a good roughening effect. If the second roughening treatment time is too long, on the one hand, it will generate high energy consumption, and on the other hand, it may cause excessive damage to the copper foil layer of the carrier copper foil, affecting the performance of the copper foil layer. Optionally, the second roughening treatment time can be 10S, 20S, 30S, 40S, 50S, etc.
[0106] In some embodiments, the first roughening treatment and the second roughening treatment are respectively performed in two adjacent roughening tanks, and the two adjacent roughening tanks contain roughening solutions respectively. The first roughening treatment and the second roughening treatment are respectively performed in two adjacent roughening tanks to obtain a more sufficient roughening effect, so that the copper foil layer of the carrier copper foil has both a larger surface area and better surface consistency.
[0107] Please see Figure 1 In another embodiment of the present disclosure, a carrier copper foil roughening device 1 is provided. The carrier copper foil roughening device 1 comprises a first roughening tank 2 and a second roughening tank 3 which are sequentially arranged along the transmission direction of the first carrier copper foil 5. Roughening solution and roughening solution are contained in the first roughening tank and the second roughening tank, respectively. The carrier copper foil is subjected to a first roughening treatment and a second roughening treatment in the first roughening tank and the second roughening tank, respectively. The solution, solution temperature, current density, treatment time, etc. used in the first roughening treatment and the second roughening treatment can be selected accordingly from the parameters listed above, and will not be repeated here.
[0108] It can be understood that the carrier copper foil roughening device further includes a transfer roller 4, through which the first carrier copper foil 5 is sequentially transferred to the first roughening tank and the second roughening tank.
[0109] The present disclosure also provides a carrier copper foil, which is prepared by the above-mentioned carrier copper foil preparation method.
[0110] The present disclosure also provides an electronic product, comprising the above-mentioned carrier copper foil. Optionally, the electronic product comprises a printed circuit board (PCB), an integrated circuit board, etc.
[0111] It is understood that when preparing an electronic product, the copper foil layer of the carrier copper foil is combined with the electronic product substrate, and then the peeling layer is removed. When removing the peeling layer, the carrier layer is peeled off together with the peeling layer, thereby obtaining an electronic product including an ultra-thin copper foil layer.
[0112] The carrier copper foil can be a single-sided rough copper foil or a double-sided smooth copper foil. Conventional production equipment can only form a single-sided rough copper foil, but the integrated carrier copper foil production equipment disclosed in the present invention can form copper foil on both sides of the carrier layer to obtain a carrier copper foil with double-sided smooth copper foil.
[0113] The integrated carrier copper foil production equipment disclosed in the present invention can continuously produce three key processes, namely, foil production, peeling layer preparation, and main copper foil production, and omits the winding and unwinding logistics links between the work sections in the traditional process. The key to this innovative technology is the process of online preparation of the peeling layer. In the existing production process, it is necessary to configure a sputtering or electrophoresis device outside the foil production line to form the peeling layer, and the online preparation of the peeling layer cannot be achieved due to process limitations.
[0114] The carrier copper foil of the present disclosure is further described below.
[0115] Figure 2 The schematic diagram of the structure of a second carrier copper foil 6 in the embodiment of the present disclosure is shown, which specifically includes a carrier layer 61, a peeling layer 62 and a copper foil layer 63. It is understood that during the preparation of the carrier copper foil, the surface of the copper foil layer 63 can be subjected to an anti-oxidation treatment using the anti-oxidation solution of the present disclosure.
[0116] Further, Figure 2 In the figure, the S surface represents the non-cathode roller surface of the carrier copper foil, which is also called the non-pressing surface or S surface (Smooth surface). The M surface represents the cathode roller surface of the carrier copper foil, which is also called the pressing surface or M surface (Matte surface). In this embodiment, the peeling layer 62 is formed on the non-cathode roller surface of the carrier layer 61. It can be seen that the present disclosure is a method for preparing a strippable copper layer on the non-cathode roller surface. Compared with the prior art method for preparing a strippable copper layer on the cathode roller surface, the present method has the following significant technical advantages:
[0117] Specifically, preparing a peeling layer on the non-cathode roller surface can make the back of the carrier copper foil finished product smooth, so as to obtain a double-sided smooth carrier copper foil product, which provides greater flexibility for the application of copper foil. When preparing a strippable copper layer on the cathode roller surface, it is difficult to generate the required roughness on the other side of the copper foil (non-cathode roller surface) due to the smooth surface of the cathode roller. This limits the performance of copper foil in certain applications. By preparing a strippable copper layer on the non-cathode roller surface, we can use specific process conditions (such as brush plating technology) to generate the required roughness on this side. This not only improves the adhesion of the copper foil, but also enhances the stability of the carrier layer in subsequent processing. For example, in the manufacturing process of printed circuit boards, the increase in roughness can significantly improve the bonding strength between the carrier layer copper foil and the substrate, reducing the risk of peeling after lamination. From the surface, the carrier layer can still be used as copper foil.
[0118] By preparing a strippable copper layer on the non-cathode roller surface and using a double-stripping technique to generate a double stripping layer, the thickness and roughness of the coating can be controlled more accurately. Specifically, the first brush plating generates a phosphating film, and the second brush plating generates a phosphating metal layer. This method not only ensures the uniformity of the coating, but also achieves fine control of the roughness by adjusting the pressure, speed and current of the brush plating roller. This is particularly important in high-end applications, because uniform coating and controllable roughness can significantly improve the performance and reliability of copper foil.
[0119] The present invention not only solves the shortcomings of the prior art in generating a double-sided optical carrier layer and ensuring the roughness of the back of the carrier layer by preparing a strippable copper layer on the non-cathode roller surface and combining the double stripping layer technology, but also significantly improves the performance and application range of the copper foil by precisely controlling the uniformity and roughness of the coating. This provides a more reliable and efficient solution for the manufacture of high-end electronic products.
[0120] In the disclosed embodiment, the stripping layer 62 includes a first brush-plated layer 621 formed by the first brush plating and a second brush-plated layer 622 formed by the second brush plating. Specifically, the first brush-plated layer 621 is a phosphating film formed by using liquid medicine A, and the second brush-plated layer 622 is a phosphide layer formed by using liquid medicine B. In the process of forming the phosphide layer, an anti-oxidation treatment reaction is also included with the non-cathode roller surface of the carrier layer, and the non-cathode roller surface of the carrier layer can also be surface treated.
[0121] In the embodiment of the present disclosure, the stripping layer 62 includes a first brush-plated layer 621 formed by the first brush-plating and a second brush-plated layer 622 formed by the second brush-plating. By preparing the stripping layer 62 on the non-cathode roller surface, the first brush-plated layer 621 is formed into a phosphating film using a liquid medicine A. The formation of the phosphating film not only provides a good foundation for the subsequent second brush-plated layer 622, but also can improve the surface characteristics of the non-cathode roller surface of the carrier layer to a certain extent, and improve its uniformity and flatness.
[0122] The second brush plating layer 622 uses liquid medicine B to form a phosphide layer. During the formation of the phosphide layer, the metal ions in liquid medicine B are reduced and deposited on the surface of the phosphide film to form a uniform phosphide layer. This process not only ensures the thickness and uniformity of the stripping layer, but also achieves fine control of the roughness of the phosphide layer by adjusting the pressure, speed and current of the brush plating roller.
[0123] During the formation of the phosphide layer, an anti-oxidation treatment reaction occurs between the components in the solution B and the non-cathode roller surface of the carrier layer. This reaction effectively prevents the oxidation of the non-cathode roller surface of the carrier layer during preparation and storage, ensuring the quality and performance of the copper foil surface.
[0124] While the phosphide layer is being generated, the non-cathode roller surface of the carrier layer can also be surface treated. By adjusting the composition of solution B and brush plating conditions, the roughness and adhesion of the non-cathode roller surface of the carrier layer can be further improved, thereby improving its stability and reliability in subsequent processing.
[0125] This embodiment prepares the peeling layer 62 on the non-cathode roller surface, combines the double brush plating technology and anti-oxidation treatment, not only ensures the uniformity and roughness of the peeling layer, but also improves the surface quality and performance of the copper foil. This provides a more reliable and efficient solution for the manufacture of high-end electronic products.
[0126] The present disclosure mainly proposes a technical solution for forming a peeling layer by depositing a solution within a range. It is obvious to those skilled in the art that the deposition formation can have various variations, including but not limited to immersion, dip coating, brush coating, spray coating, overcoating, plating, roller plating, hanging plating and other methods to apply the solvent to the preset surface of the carrier layer. In addition, the equipment using the above scheme is not limited to a one-piece machine for preparing the raw foil of the carrier foil and the post-processing equipment online or a segmented non-one-piece machine for preparing the raw foil and the post-processing equipment.
[0127] Through these different deposition methods and equipment configurations, the technical solution of the present disclosure can flexibly adapt to different production and process requirements, ensuring that a high-quality peeling layer is prepared on the preset surface of the carrier layer. Regardless of which specific deposition method or equipment type is used, as long as the peeling layer is prepared on the preset surface of the carrier layer by the above method, it falls within the protection scope of the present disclosure.
[0128] Among them, the thickness of the copper foil layer is 0.5μm to 5μm. The copper foil layer with a thickness in this range can meet the thickness requirements of electronic products for ultra-thin copper foil layers. At the same time, the copper foil layer has a high elongation, so it has a good application prospect. Optionally, the thickness of the copper foil layer can be 0.5μm, 1μm, 1.5μm, 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm, 5μm, etc. It is understandable that the thickness of the copper foil layer can also be other suitable choices within the range of 0.5μm to 5μm.
[0129] When the thickness of the copper foil layer is 1.5 μm, the unit area weight of the carrier copper foil can be 18 g / m 2 Up to 22g / m 2 When the thickness of the copper foil layer is 3 μm, the unit area weight of the carrier copper foil can be 31 g / m 2 Up to 35g / m 2 When the thickness of the copper foil layer is 5 μm, the unit area weight of the carrier copper foil can be 48 g / m 2 Up to 54g / m 2range; of course, in other embodiments of the present disclosure, the unit area weight of the carrier copper foil can also be other suitable values. Exemplarily, the roughness of the copper foil layer on the side close to the carrier layer is less than 2μm, and the roughness of the copper foil layer on the side away from the carrier layer is also less than 2μm, the thickness of the carrier layer is 18μm, and the peel strength of the peeling layer at room temperature is not less than 3g / cm, and not more than 30g / cm. The carrier copper foil has the characteristics of ultra-thinness, low roughness, high peel strength and good etching properties, and is suitable for other suitable application scenarios such as high-frequency and high-speed copper clad laminates, flexible printed circuit boards, and high-density interconnect technology boards.
[0130] The performance indicators of the carrier copper foil of the present invention were tested, and the results are shown in Table 1. It can be seen that the carrier copper foil of the present invention has excellent thickness, roughness, peel strength, etc. and has good customizability.
[0131] Table 1
[0132]
[0133] Example 1-1
[0134] The preparation method of the carrier copper foil in this embodiment includes:
[0135] S1: preparing a peeling layer on the surface of the carrier layer to obtain a first pre-finished product.
[0136] Specifically, S101: performing surface treatment on the carrier copper layer to remove oil stains, impurities, etc. on the surface.
[0137] S102: using liquid A to perform a first brush plating without charge on the surface of the carrier layer to form a phosphating film on the surface of the carrier layer. The temperature of liquid A is 20° C., and the pH value of liquid A is 1. The speed of the first brush plating is 1 m / min, and the time of the first brush plating is 5 s. The composition of liquid A is: 0.1 g / L zinc dihydrogen phosphate.
[0138] S103: Use liquid medicine B to perform a second charged brush plating on the surface of the phosphating film away from the carrier layer to form a phosphide layer on the surface of the phosphating film. The temperature of liquid medicine B is 30°C, and the pH value of liquid medicine B is 1. The second pulse period is 1:6, the current density is 0.2A / square decimeter, the speed of the second brush plating is 1m / min, and the time of the second brush plating is 10min. The composition of liquid medicine B is: 0.2g / L chromium phosphide. A first pre-finished product is obtained.
[0139] S2: preparing a copper foil layer on the surface of the first pre-finished product to obtain a second pre-finished product.
[0140] Specifically, S201: electroplating the first pre-finished product with a copper electroplating solution to deposit the copper foil layer on the side of the stripping layer away from the carrier layer. The copper electroplating solution comprises: 20 g / L phytic acid, 10 g / L copper carbonate, 0.3 g / L tartaric acid additive, and the solvent is water. The pH value of the copper electroplating solution is 2. When preparing the copper foil layer, the electroplating temperature is 40°C, the rate is 0.6 m / min, and the current density is 3 A / dm 2 The thickness of the copper foil layer is 5 microns.
[0141] S3: roughening the copper foil layer.
[0142] Specifically, S301: performing a first roughening treatment and a second roughening treatment on the second pre-finished product in sequence; the first roughening treatment uses a first roughening solution, and the second roughening treatment uses a second roughening solution.
[0143] The first roughening solution is the same as the second roughening solution. The components of the roughening solution are: 22 g / L copper, 40 g / L sulfuric acid, 0.4 g / L carbon nanotubes, and the solvent is water.
[0144] use Figure 1 The roughening equipment shown in the figure performs the first roughening treatment and the second roughening treatment on the carrier copper foil in sequence. In the first roughening treatment, the temperature of the roughening solution is 18°C, the current density is 80A / square decimeter, and the time of the first roughening treatment is 18S. In the second roughening treatment, the temperature of the roughening solution is 18°C, the current density is 20A / square decimeter, and the time of the second roughening treatment is 18S.
[0145] S4: using an anti-oxidation liquid to perform an anti-oxidation treatment on the roughened second pre-finished product.
[0146] Specifically, S401: using an anti-oxidation solution to perform an anti-oxidation treatment on the second pre-finished product. The components of the anti-oxidation solution are: phytic acid 2g / L, zinc 5g / L, nickel 2g / L, nitric acid 2g / L and water. The current density of the anti-oxidation treatment is 5A / dm 2 The temperature of the anti-oxidation treatment was 22° C. The conveying speed of the second pre-product during the anti-oxidation treatment was 8 m / min.
[0147] The differences between Examples 1-2 to 1-5, Comparative Example 1-1 and Example 1-1 are shown in Table 2.
[0148] Test Case
[0149] The carrier copper foils obtained in Examples 1-1 to 1-5 and Comparative Example 1-1 were hot pressed with the epoxy resin substrate at 200° C. for 1 hour. The bonding strength between the carrier copper foil and the substrate was then tested, and the results are shown in Table 2.
[0150] Table 2
[0151]
[0152] It can be seen from Table 2 that the anti-oxidation treatment of the carrier copper foil using the anti-oxidation solution disclosed in the present invention can effectively improve the bonding strength between the carrier copper foil and the substrate.
[0153] Example 2-1
[0154] Compared with Example 1-1, Example 2-1 is different in that: the component of potion A is: 5 g / L zinc dihydrogen phosphate. The component of potion B is: 10 g / L chromium phosphide.
[0155] Example 2-2
[0156] Compared with Example 1-1, Example 2-2 is different in that: the component of potion A is: 10 g / L zinc dihydrogen phosphate. The component of potion B is: 20 g / L chromium phosphide.
[0157] Comparative Example 2-1
[0158] Compared with Example 1, Comparative Example 2-1 is different in that the first brush plating is not included.
[0159] Comparative Example 2-2
[0160] Compared with Example 1, Comparative Example 2-2 is different in that the second brush plating is not included.
[0161] Comparative Examples 2-3
[0162] The preparation method of the carrier copper foil in Comparative Example 2-3 is:
[0163] S101: Surface treatment is performed on the carrier copper layer to remove oil stains, impurities, etc. on the surface.
[0164] S102: preparing a peeling layer on the surface of the carrier layer by electrophoresis.
[0165] S103: depositing an ultra-thin copper layer with a thickness of 5 microns on the surface of the peeling layer.
[0166] Comparative Examples 2-4
[0167] The preparation method of the carrier copper foil in Comparative Example 2-4 is:
[0168] S101: Surface treatment is performed on the carrier copper layer to remove oil stains, impurities, etc. on the surface.
[0169] S102: preparing a peeling layer on the surface of the carrier layer by sputtering.
[0170] S103: depositing an ultra-thin copper layer with a thickness of 5 microns on the surface of the peeling layer.
[0171] Test Case
[0172] The copper layer of the carrier copper foil prepared in the examples and comparative examples was attached to the surface of the substrate. Then the peeling force of the peeling layer and the copper foil was tested, as well as the residual state of the peeling layer. Peeling force test conditions: 200°C, 20kg / cm 2 The pressing was carried out for 3 hours. The results are shown in Table 3 below.
[0173] Table 3
[0174]
[0175] As can be seen from Table 3, in the embodiment, the peeling force when peeling the peeling layer from the copper foil is less than that in the comparative example, indicating that the peeling layer obtained by the peeling layer solution disclosed in the present invention is easier to peel from the copper foil. In addition, when peeling the layer, the peeling layer in the embodiment has no residue, while the peeling layer in the comparative example has a small amount of residue, indicating that the peeling layer obtained by the peeling layer solution disclosed in the present invention is not only easier to peel, but also has no residue after peeling, which will not affect the subsequent use of the ultra-thin copper layer.
[0176] Example 3-1
[0177] Compared with Example 1-1, the difference of this example is that the concentration of phytic acid is 50 g / L and the concentration of copper carbonate is 10 g / L.
[0178] Example 3-2
[0179] Compared with Example 1-1, the difference of this example is that the concentration of phytic acid is 100 g / L and the concentration of copper carbonate is 10 g / L.
[0180] Example 3-3
[0181] Compared with Example 1-1, the difference of this example is that the concentration of phytic acid is 50 g / L and the concentration of copper carbonate is 50 g / L.
[0182] Embodiment 3-4
[0183] Compared with Example 1-1, the difference of this example is that the concentration of phytic acid is 50 g / L and the concentration of copper carbonate is 80 g / L.
[0184] Comparative Example 3-1
[0185] Compared with Example 1-1, the difference of this comparative example is that the copper electrodeposition solution is: 130 g / L potassium pyrophosphate, 25 g / L copper, 2 g / L citric acid additive, the solvent is water, and the pH value is 8.5.
[0186] The elongation of the copper foil layer obtained in the embodiment and the comparative example was tested, and the results are shown in Table 4:
[0187] Table 4
[0188]
[0189] It can be seen from Table 4 that the combination of phytic acid and copper carbonate in the present disclosure can effectively improve the elongation of the copper foil layer.
[0190] Examples 4-1 to 4-5
[0191] Compared with Example 1-1, the difference between Examples 4-1 to 4-5 is that the roughening solutions are different, and the specific differences are shown in Table 5.
[0192] Embodiment 4-6
[0193] Compared with Example 1-1, the difference of this example is that the carbon nanotubes are replaced with zinc sulfate.
[0194] Comparative Examples 4-1 to 4-3
[0195] Compared with Example 1-1, the difference between Comparative Examples 4-1 to 4-3 is that the roughening solutions are different, and the specific differences are shown in Table 5.
[0196] The surface roughness (Rz, in micrometers) of the copper foil layer of the carrier copper foil obtained in the examples and comparative examples was tested, and the results are shown in Table 5. The peel strength (in kg / cm) between the roughened surface of the carrier copper foil obtained in the examples and comparative examples and the epoxy resin substrate was tested, and the results are shown in Table 5.
[0197] Table 5
[0198]
[0199] It can be seen from Table 5 that the peel strength between the roughened surface of the carrier copper foil and the substrate in the example is greater than that in the comparative example, indicating that the roughening solution disclosed in the present invention can effectively improve the bonding strength between the carrier copper foil and the substrate.
[0200] It should be understood that the present disclosure does not limit its application to the detailed structure and arrangement of the components proposed in the present disclosure. The present disclosure can have other embodiments and can be implemented and executed in a variety of ways. The aforementioned variations and modifications fall within the scope of the present disclosure. It should be understood that the present disclosure and the limited present disclosure extend to all alternative combinations of two or more individual features mentioned or evident in the text and / or the drawings. All of these different combinations constitute multiple alternative aspects of the present disclosure. The embodiments described in the present disclosure illustrate the best modes known for implementing the present disclosure and will enable those skilled in the art to utilize the present disclosure.
Claims
1. A carrier copper foil anti-oxidation solution, characterized in that: The invention comprises the following components: phytic acid 1g / L-5g / L, zinc 1g / L-10g / L, nickel 1g / L-5g / L, nitric acid 0.1g / L-5g / L and solvent.
2. The carrier copper foil anti-oxidation solution according to claim 1, characterized in that: The concentration of chromium in the carrier copper foil anti-oxidation solution is 0.
3. The carrier copper foil anti-oxidation solution according to claim 1, characterized in that: The pH value of the carrier copper foil anti-oxidation solution is 1-5.
4. The carrier copper foil anti-oxidation solution according to any one of claims 1 to 3, characterized in that: The solvent is water.
5. A method for preparing a carrier copper foil, characterized in that: The steps include: Prepare a peeling layer on the surface of the carrier layer to obtain a first pre-finished product; Preparing a copper foil layer on a side of the release layer of the first pre-finished product away from the carrier layer to obtain a second pre-finished product; The surface of the copper foil layer of the second pre-finished product is subjected to an anti-oxidation treatment using the carrier copper foil anti-oxidation solution according to any one of claims 1 to 4.
6. The method for preparing a carrier copper foil according to claim 5, characterized in that: The current density of the anti-oxidation treatment is 0.1A / dm 2 ~10A / dm 2 .
7. The method for preparing a carrier copper foil according to claim 5, characterized in that: The temperature of the anti-oxidation treatment is 20°C to 25°C.
8. The method for preparing a carrier copper foil according to any one of claims 5 to 7, characterized in that: The transmission speed of the second pre-product during the anti-oxidation treatment is 0.2 m / min to 15 m / min.
9. A carrier copper foil, characterized in that: The method is prepared by the preparation method described in any one of claims 5 to 8.
10. An electronic product, characterized in that: The copper foil layer comprises the carrier copper foil according to claim 9.